1987
DOI: 10.1002/bit.260300216
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐catalyzed ester exchange reactions in organic media with controlled humidity

Abstract: Immobilized lipase activity is studied in organic solvent systems of controlled water content under the influence of a variety of reaction parameters, such as temperature, relative humidity, substrate concentrations, and type of fatty acid used. Control of the amount of water in the reaction system was found to be a valuable tool for the orientation of the reaction process and for the determination of the final reaction products. The properties of the immobilized lipase were studied using the interesterificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(72 citation statements)
references
References 30 publications
3
64
1
4
Order By: Relevance
“…By using water-miscible organic solvents like glycerol [34], almost 'dry' reverse micelles were created in which solubilized enzymes display a high level of catalytic activity. Considerable activity was recorded also at the lowest water activity tested (a, 0.3) in the lipase-catalyzed hydrolysis of triolein in n-hexane [35] and at a water activity of approximately a, 0.4 in the lipase-catalyzed alcoholysis reaction [36].…”
Section: Discussionmentioning
confidence: 99%
“…By using water-miscible organic solvents like glycerol [34], almost 'dry' reverse micelles were created in which solubilized enzymes display a high level of catalytic activity. Considerable activity was recorded also at the lowest water activity tested (a, 0.3) in the lipase-catalyzed hydrolysis of triolein in n-hexane [35] and at a water activity of approximately a, 0.4 in the lipase-catalyzed alcoholysis reaction [36].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial lipases constitute an important group of biotechnologically valuable enzymes, mainly because of versatility of their applied properties and ease of mass production (13,28,42). Besides their industrial applications, novel biotechnological applications have been successfully established using lipases for the synthesis of biopolymers and biodiesel, the production of enantiopure pharmaceuticals, agrochemicals and flavor compounds (16).…”
Section: Introductionmentioning
confidence: 99%
“…Use of Molecular Sieves: The initial water activities of the substrates were adjusted according to Goderis et al 27 by adding the molecular sieves in the reaction mixture. It was found that the esterification reaction was stable when mass equivalent of molecular sieves was used.…”
Section: Resultsmentioning
confidence: 99%